Efecto antidiabético y toxicidad aguda del extracto acuoso del Phyllanrhus sellowianus Müller Arg. - Oksana Hnatyszyn; Jorge Miño; Susana Gorzalczany; Graciela Ferraro; Jorge D. Coussio; Cristina Acevedo
No disponible